Women decision-making capacity and intimate partner violence among women in sub-Saharan Africa - Bright Opoku Ahinkorah; Kwamena Sekyi Dickson; Abdul-Aziz Seidu (BMC, 2018)
Abstract Background Violence against women is a common form of human rights violation, and intimate partner violence (IPV) appears to be the most significant component of violence. The aim of this study was to examine the association between women decision-making capacity and IPV among Women in Sub-Saharan Africa. The study also looked at how socio-demographic factors also influence IPV among Women in Sub-Saharan Africa. Methods The study made use of pooled data from most recent Demographic and Health Survey (DHS) conducted from January 1, 2010, and December 3, 2016, in 18 countries in Sub-Saharan Africa. For the purpose of the study, only women aged 15-49 were used (N = 84,486). Univariate and multivariate logistic regression models were used to investigate the relationship between the explanatory variables and the outcome variable. Results The odds of reporting ever experienced IPV was higher among women with decision-making capacity [AOR = 1.35; CI = 1.35-1.48]. The likelihood of experiencing IPV was low among young women. Women who belong to other religious groups and Christians were more likely to experience IPV compared to those who were Muslims [AOR = 1.73; CI = 1.65-1.82] and [AOR = 1.87; CI = 1.72-2.02] respectively. Women who have partners with no education [AOR = 1.11; CI = 1.03-1.20], those whose partners had primary education [AOR = 1.34; CI = 1.25-1.44] and those whose partners had secondary education [AOR = 1.22; CI = 1.15-1.30] were more likely to IPV compared to those whose partners had higher education. The odds of experiencing IPV were high among women who were employed compared to those who were unemployed [AOR = 1.33; CI = 1.28-1.37]. The likelihood of the occurrence of IPV was also high among women who were cohabiting compared to those who were married [AOR = 1.16; CI = 1.10-1.21]. Women with no education [AOR = 1.37; CI = 1.24-1.51], those with primary education [AOR = 1.65; CI = 1.50-1.82] and those with secondary education [AOR = 1.50; CI = 1.37-1.64] were more likely to experience IPV compared to those with higher education. Finally, women with poorest wealth status [AOR = 1.28; CI = 1.20-1.37], those with poorer wealth status [AOR = 1.24; CI = 1.17-1.32], those with middle wealth status [AOR = 1.27; CI = 1.20-1.34] and those with richer wealth status [AOR = 1.11; CI = 1.06-1.17] were more likely to IPV compared to women with richest wealth status. Conclusion Though related socio-demographic characteristics and women decision-making capacity provided an explanation of IPV among women in sub-Saharan Africa, there were differences in relation to how each socio-demographic variable predisposed women to IPV in Sub-Saharan Africa.